Investigation on Decontaminating Efficiency of N,N-Dichloropolystyrene Sulfonamide Nanofibers against Pathogenic Bacteria of Human Body Flora - Maddah, B.; Azimi, M.; Imani, S.; Zand, A.M.; Borna, H.; Sharifi, M. (Asian Journal of Chemistry, 2012)
N,N-Dichloropolystyrene sulfonamide as a decontaminating agent against pathogenic bacteria that could be synthesized during five steps from styrene precursor. Structures of products of each step were characterized by FT-IR technique and finally the active chlorine (Cl+) contents were checked by standard iodometry titration and determined to be 10 to 26 %. Nanofibers of N,N-dichloropolystyrene sulfonamide were electrospined from mixture of polystyrene: N,N-dichloropolystyrene sulfonamide (1:5) in DMF. Diameters of these fibers were estimated to be about 160-1900 nm by scanning electron microscopy (SEM). The decontaminant efficiency of these fibers was evaluated by treatment of three standard pathogenic bacteria such as Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. The results of this study, represented the bactericidal ability of N,N-dichloropolystyrene sulfonamide nanofibers.